TNF-α, VEGF, and Procalcitonin Levels Dynamic Changes During Severe Traumatic Brain Injury - Diya Hasan; Mu’ad Alzuabe; Yazan Ismail; Ahmad Al Tibi; Amid Abdelnour (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: The variety of traumatic brain injury (TBI) creates difficulty in evaluating its level and the clinical outcome correctly. This study aimed to analyze the level variations and dynamic of serum biomarkers, such as tumor necrosis factor (TNF)-α, vascular endothelial growth factor (VEGF), and procalcitonin (PCT) in response to severe TBI.METHODS: Intravenous blood samples were collected from 20 TBI subjects at different time points: 0, 12, 24, and 48 hours. The serum levels of TNF-α, VEGF, and PCT were measured using specific monoclonal antibodies by quantitative sandwich enzyme-linked immunosorbent assay (ELISA).RESULTS: In 0, 12, 24, and 48 hours, the serum levels were significantly higher for TNF-α (p<0.0001), VEGF (p<0.0001) and PCT (p<0.0001) compared to the healthy control. In comparison to admission time point, TNF-α had elevated significantly (p<0.001) at 24 hours. PCT showed a significant increase after 48 hours (p<0.02) and VEGF showed no significant differences. Comparing the 3 biomarkers dynamic changes at 0, 12 and 24 hours, PCT level showed to be lower than VEGF and TNF-α levels, while VEGF level showed to be higher than PCT and TNF-α levels. However after 48 hours, PCT level (0.25 ng/mL) had elevated more than VEGF (0.21 ng/mL) and TNF- α (0.18 ng/mL) levels.CONCLUSION: Monitoring PCT in comparison to VEGF and TNF-α can be used to assist the progress of severe TBI, since PCT level progressive changes were associated with time increase.KEYWORDS: trauma, TNF-α, VEGF, PCT, Glasgow Coma Scale